Environmental complexity and the purging of deleterious alleles. (1st November 2017) - Singh, Amardeep; Agrawal, Aneil F.; Rundle, Howard D.
Abstract: Sexual interactions among adults can generate selection on both males and females with genome‐wide consequences. Sexual selection through males is one component of this selection that has been argued to play an important role in purging deleterious alleles. A common technique to assess the influence of sexual selection is by a comparison of experimental evolution under enforced monogamy versus polygamy. Mixed results from past studies may be due to the use of highly simplified laboratory conditions that alter the nature of sexual interactions. Here, we examine the rate of purging of 22 gene disruption mutations in experimental polygamous populations of Drosophila melanogaster in each of two mating environments: a simple, high‐density environment (i.e., typical fly vials), and a lower density, more spatially complex environment. Based on past work, we expect sexual interactions in the latter environment to result in stronger selection in both sexes. Consistent with this, we find that mutations tend to be purged more quickly in populations evolving in complex environments. We discuss possible mechanisms by which environmental complexity might modulate the rate at which deleterious alleles are purged and putatively ascribe a role for sexual interactions in explaining the treatment differences in our experiment.